Studi Komparasi Yuridis Perkawinan Beda Agama Antara Indonesia Dengan Singapura Berdasarkan Hukum Perdata - Alexandra Goldine Sihombing, Yohana; Azizah, Azizah; Ghudzamir, Akmal; Imaniyar, Nadhira; Dzil Izzati, Inayatu; Aryanti Ramadhani, Dwi (Zaaken: Journal of Civil and Business Law, 2025)
Interfaith marriages often occur in several countries such as Indonesia and Singapore. The regulations applied in each country regarding interfaith marriages often differ, leading individuals who wish to enter into interfaith marriages to change their citizenship or follow their partner who holds citizenship in a country with legal provisions allowing interfaith marriages. This research will discuss the application of comparative law on interfaith marriages between Indonesia and Singapore along with its cases using a normative juridical research method with a qualitative approach consisting of legal, case, and comparative approaches. This research aims to analyze the comparison of applicable laws in Indonesia and Singapore in a specific case. This research will compare the civil law foundations of both countries to identify the strengths and weaknesses of each regarding interfaith marriages occurring among their citizens. Interfaith marriages that occur between Indonesia and Singapore also serve as a guideline in the case study in Indonesia based on judicial decisions and the guidelines for interfaith marriages conducted in Singapore, thereby providing legality with permanent and binding legal force.